2021
DOI: 10.3399/bjgp.2020.0948
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of remote consulting in UK primary care following the COVID-19 pandemic: a mixed-methods longitudinal study

Abstract: Background: To reduce contagion of COVID-19, in March 2020 UK general practices implemented predominantly remote consulting via telephone, video or online consultation platforms. Aim: To investigate the rapid implementation of remote consulting and explore impact over the initial months of the COVID-19 pandemic. Design and Setting: Mixed-methods study in 21 general practices in Bristol, North Somerset and South Gloucestershire. Methods: Quantitative: Longitudinal observational analysis comparing volume and typ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
415
4
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 333 publications
(451 citation statements)
references
References 24 publications
(33 reference statements)
27
415
4
5
Order By: Relevance
“…2 Studies highlighted that remote consultations in primary care rapidly increased during the pandemic, changing management of patients. 4 We have some understanding of challenges facing PCPs during other pandemics. Previous work during influenza, Ebola and SARS pandemics showed that primary care professionals (PCPs) want to help in a pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…2 Studies highlighted that remote consultations in primary care rapidly increased during the pandemic, changing management of patients. 4 We have some understanding of challenges facing PCPs during other pandemics. Previous work during influenza, Ebola and SARS pandemics showed that primary care professionals (PCPs) want to help in a pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of lockdowns in the UK resulted in the majority of medical consultations in primary care shifting to audio or video encounters with patients [ 30 , 31 ]. Lockdown-specific barriers to disclosure of abuse [ 32 ] and barriers to general practice consultations linked to the system switch to remote consulting [ 33 ] have occurred at the same time as the incidence of abuse has increased [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…These were collected as part of the mixed-methods RAPCI (Rapid COVID-19 intelligence to improve primary care response) Study, the results of which are reported elsewhere. 16…”
Section: Methodsmentioning
confidence: 99%
“…These were collected as part of the mixed-methods RAPCI (Rapid COVID-19 intelligence to improve primary care response) Study, the results of which are reported elsewhere. 16 Recruitment Practices in BNSSG were provided with study information by the CCG. Expressions of interest were received from practices and a selection were recruited, ensuring a mix of practice sizes and deprivation scores.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation